Shoulder Adhesive Capsulitis in Type 1 Diabetes Mellitus: A Cross-Sectional Study on 943 Cases in Sardinian People - Doria, Carlo; Mosele, Giulia R.; Badessi, Francesca; Puddu, Leonardo; Caggiari, Gianfilippo (Joints, 2017)
Purpose To evaluate the prevalence of adhesive capsulitis (AC) of the shoulder in patients with type 1 diabetes mellitus (T1DM) in Sardinia.Methods In this cross-sectional study, we evaluated 943 patients with T1DM attending the division of Endocrinology and Metabolism at the University Hospital in Sassari, Italy. The criteria for diagnosing AC were: pain for at least 1 month, inability to lie on the affected shoulder, and restricted active and passive shoulder joint movements in at least three planes. Age, gender, duration of DM, blood pressure, and presence of neuropathy and retinopathy were noted. Metabolic control of DM was evaluated with glycosylated hemoglobin A1c (GHbA1c) blood concentrations.Results AC was diagnosed in 331 patients (prevalence: 35.1%). Age, duration of DM, high blood pressure levels, and the presence of neuropathy and retinopathy were significantly associated with AC. No significant association was observed between gender and AC. There was no significant difference in mean levels of GHbA1c in T1DM patients with or without AC.Conclusion This study shows that AC of the shoulder is a common disorder in patients with T1DM in Sardinia. It is significantly associated with age, duration of DM, and related complications.Level of Evidence Level IV, observational cross-sectional study.
Keywords: adhesive capsulitis; diabetes mellitus; prevalence; Sardinia; shoulder